A new strategy for direct solution electrospinning of phosphorylated poly(vinyl chloride)/polyethyleneimine blend in alcohol media. (19th January 2023) - Altinkok, Cagatay; Sagdic, Gokhan; Daglar, Ozgun; Ercan Ayra, Merve; Yuksel Durmaz, Yasemin; Durmaz, Hakan; Acik, Gokhan
Graphical abstract: Highlights: A very promising strategy for preparing poly(vinyl chloride)/polyethyleneimine based electrospun nanofiber mat is described. The electrospun nanofiber mats exhibit smooth and completely bead-free alignment. The electrospun nanofiber mats provide a safer surface for platelet with lower hemolytic activity. Abstract: Phosphorylated poly(vinyl chloride) (PPVC)/polyethyleneimine (PEI)-based nanofibers were produced via electrospinning in their blended solutions for the first time. For this purpose, PVC was partially converted into PVC-N3 and the PVC-N3 is then reacted with bis(diethoxyphosphoryl) acetylene (BDPA) via metal-free azide–alkyne 1, 3-dipolar cycloaddition reaction to achieve the alcohol-soluble PPVC. PPVC and PEI solutions at certain concentrations prepared in methanol were electrospun from a single syringe at 90/10 and 85/15 vol ratios without phase separation. The accuracy of the modifications conducted on PVC was proven by Fourier-transform infrared (FT-IR), proton and carbon nuclear magnetic resonance ( 1 H NMR and 13 C NMR) spectroscopies and gel permeation chromatography (GPC), respectively. The achieved nanofibers and their intermediates were characterized by scanning electron microscope (SEM), water contact angle (WCA) measurement, thermogravimetric (TGA) and differential scanning calorimetry (DSC) analyses. The blood interaction of PPVC-PEI was evaluated through hemolysis and platelet activation assay, since most of the biomedical applications of PVC derivatives have close contact with blood. The results showed that PPVC-PEI nanofibers provide a safer surface for platelet with lower hemolytic activity compared to PPVC nanofibers. Therefore, PPVC-PEI-based electrospun nanofibers obtained by such an effective strategy exhibited a promising perspective for scientists in various biomedical purposes.